2020
DOI: 10.1016/j.jdeveco.2020.102445
|View full text |Cite
|
Sign up to set email alerts
|

Using social connections and financial incentives to solve coordination failure: A quasi-field experiment in India's manufacturing sector

Abstract: Production processes are often organized in teams, yet there is limited evidence on whether and how social connections and financial incentives affect productivity in tasks that require coordination among workers. We simulate assembly line production in a lab-in-the-field experiment in which workers exert real effort in a minimum-effort game in teams whose members are either socially connected or unconnected and are paid according to the group output. We find that group output increases by 18% and coordination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
(35 reference statements)
0
18
0
Order By: Relevance
“…HR managers can improve their understanding of the salience of group identifies (Chen & Li, 2009), and social norms of groups or ‘tribe’ could be employed to influence employee behaviour to align with the organisation’s goals. In a recent study, Afridi et al (2020) simulate assembly line production in an experimental set up in which workers exerted real effort in teams whose members are either socially connected or unconnected and are paid according to the group output. They found that group output significantly increased by 18%, and coordination improved by 30%–39% when workers are socially connected with their co-workers.…”
Section: Behavioural Insights For Solutionsmentioning
confidence: 99%
“…HR managers can improve their understanding of the salience of group identifies (Chen & Li, 2009), and social norms of groups or ‘tribe’ could be employed to influence employee behaviour to align with the organisation’s goals. In a recent study, Afridi et al (2020) simulate assembly line production in an experimental set up in which workers exerted real effort in teams whose members are either socially connected or unconnected and are paid according to the group output. They found that group output significantly increased by 18%, and coordination improved by 30%–39% when workers are socially connected with their co-workers.…”
Section: Behavioural Insights For Solutionsmentioning
confidence: 99%
“…When the production process is running, coordination between supervisor and employees and overall during the production process must constantly be improved so that errors affect quality degradation can be minimized (Afridi et al, 2020). Giving certain marks to the raw materials based on specifications and suppliers of origin and do double checks each time raw materials are received from suppliers to make sure meets the company's quality standard.…”
Section: Recommendationmentioning
confidence: 99%
“…Among the new studies on social environment of Indian colonial cotton mills, a significant work by Yildiz (2020) highlights the importance of the process of transition during industrialisation of the textile industry and its social consequences; like acceptance and prevalence of clock-time based work routine and its implications. Beside the literature concerning the industrial history in colonial India, our paper is also related to the newly emerging literature that examines the role of ethnic and religious identities in ensuring social cooperation using field and lab experiments (Ghosh, 2021;Afridi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%